The Many Faces of Strategic Voting : Tactical Behavior in Electoral Systems Around the World - Blais, Andre, 1947-; Aldrich, John H., 1947-; Stephenson, Laura Beth, 1976- (Book collections on Project MUSE., 2018)
"Strategic voting is classically defined as "voting for one's second preferred option to prevent one's least preferred option from winning when one's first preference has no chance." Voters want their votes to be effective, and casting a ballot that will have no influence on an election is undesirable--therefore, some voters cast a strategic ballot when they decide it is useful. This edited volume includes case studies of strategic voting behavior in Israel, Germany, Japan, Belgium, Spain, Switzerland, Canada, and the UK, and provides a conceptual framework for understanding strategic voting behavior in all types of electoral systems. The classic definition explicitly considers strategic voting in a single race with a single winner, which has at least three candidates. This situation is more common in electoral systems that have single member districts that employ plurality or majoritarian electoral rules and have multiparty systems. Indeed, much of the literature on strategic voting to date has considered systems like those in Canada and the United Kingdom. This book contributes to a more general understanding of strategic voting behavior by taking into account a wide variety of institutional contexts, such as single transferable vote rules, proportional representation, two round and mixed electoral systems"--